Molecular Expression Patterns of Virulence Factor Genes in Candida Isolates from Bloodstream Infections at A Tertiary Care Hospital - Tripathi, Shivangi; Banerjee, Gopa; Kamal, Aisha; Singh, Nitesh; Wahi, Nazia; Mohit, Mohit; Malik, Sumira; Rustagi, Sarvesh (Journal of Neonatal Surgery, 2025)
Introduction: The most prevalent fungal infection caused by Candida species which causes significant morbidity, mortality rates, and medical expenses in critically ill individuals is Candida species. Better management of Candidemia is an important phenomenon to understand the molecular epidemiology of gene expression of virulence factors and susceptibility pattern antifungal drugs. of Candida species. In this study, the distribution of Candida species, susceptibility pattern, and identification of virulence genes were performed at King George’s Medical University, India. Methods: Total of 237 Candida isolates were isolated from blood samples from tertiary care hospital during 2021 to 2022. Candida species were identified using blood culture methods, including staining, germ tube test, CHROMagar, and Corn Meal Agar, confirmed by MALDI-TOF MS. PCR was done for species identification, and virulence genes were detected. Results: Out of 237 Candida species, 26 Candida parapsilosis (26.1%), 26 Candida tropicalis (26.1%) (34),32 Candida albican (13.5%), 25 Candida auris (10.5%), 37 Candida utilis (15.6%), 12 Candida glabrata (5.06%), 2 Candida krusei (0.84%) and other species like Candida rugosa, Candida orthopsilosis, kodamaeaohmeria, Candida lustaniae, Candida guillermondii were 1(0.42%). Higher MIC values were noted for Fluconazole and Voriconazole, with Candida auris exhibiting resistance to Amphotericin B and Fluconazole. C. albicans displayed a higher frequency of virulence genes (Als1 (, HWP1, SAP) compared to non- albicans Candida. Conclusion: This present study emphasizes the significance of identifying various Candida isolates and their patterns of susceptibility, aiding clinicians in targeting antifungal treatments and reducing morbidity and mortality in Tertiary Care Unit patients.